IMPROVING STUDENTS’ ACHIEVEMENT IN WRITING PROCEDURE TEXTS THROUGH WORD WEBBING TECHNIQUE - Diah Fauzi Ningtyas; Lidiman Sinaga (Universitas Negeri Medan, 2013)
This study concerns on improving students’ achievement in writing procedure texts through word webbing technique. The research was conducted by using Classroom Action Research (CAR). The population was the 2012-2013 nine grade students of SMP Negeri 1 Batang Kuis. The number of students was 36, consisting of 21 females and 15 males. The procedure of the research was administrated into two cycles where each cycle consisted of three meetings. Each meeting included four steps namely: planning, action, observation, and reflection. There were two kinds of data collected during the study, qualitative and quantitative data. The instrument for collecting the quantitative data was the writing of procedure texts test while the qualitative data were gathered by using interview, diary notes and observation sheet. Based on the data analysis, the mean of students’ score in Test I was 53,47, for the Test II was 63,05, and for the Test III was 75 The qualitative data showed that the students were interested in the applying of Word webbing Technique. The conclusion is that Word Webbing Technique in writing Procedure Texts improves the students’ achievement in writing procedure texts. Keywords: Students’ achievement, writing, procedure text, word webbing